Identifying DNase I hypersensitive sites as driver distal regulatory elements in breast cancer - Matteo D′Antonio (Nature Portfolio, 2017)
Cancer driver mutations can occur within noncoding genomic sequences. Here, the authors develop a statistical approach to identify candidate noncoding driver mutations in DNase I hypersensitive sites in breast cancer and experimentally demonstrate they are regulatory elements of known cancer genes.